Health-Related Quality of Life and Its Associated Factors Among Burn Patients at Governmental Referral Hospitals of Amhara Regional State, Northwest Ethiopia, 2020: Institutional-Based Cross-Sectional Study - Tibebu NS; Desie T; Marew C; Wubneh M; Birhanu A; Tigabu A (Dove Medical Press, 2021)
Nigusie Selomon Tibebu,1 Tigabu Desie,1 Chalie Marew,1 Moges Wubneh,2 Adane Birhanu,2 Agimasie Tigabu2 1Department of Pediatrics and Child Health Nursing, College of Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 2Department of Adult Health Nursing, College of Health Sciences, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Tigabu DesiePediatrics and Child Health Nursing @ Debre Tabor University, P.O.Box:272, Debre Tabor, EthiopiaEmail tigabud05@gmail.comIntroduction: Burns can have a considerable negative impact on physical and psychosocial functioning that affects the quality of life. The physical and psychological manifestations may compromise the quality of life of burned patients. The aim is to assess health-related quality of life and associated factors among burn patients at Amhara regional state governmental referral hospitals, Northwest Ethiopia, 2020.Methods: Institution-based cross-sectional study was conducted from June 01 to July 15, 2020, in Amhara National regional state governmental referral hospitals. Systematic random sampling technique was used, and data were collected using structured Burn Specific Health Scale Brief Questionnaire through face-to-face interview and document review from patients time since burn 15 days and above. Data were entered into Epidata, and analysis was done by SPSS version 25. Descriptive statistics were computed, and binary logistic regression analysis was used to determine the association between the dependent and independent variables. Variables with a p-value of ≤ 0.05 in the multivariable analysis were considered statistically significant.Results: Of 423 study participants, 95.7% responded completely. Among the respondents, 58.8% (group mean and median of 18.38 and 21) for physical domain and 57% (group mean and median of 44.73 and 53) for generic domains had a poor health-related quality of life. Overall poor health-related quality of life was 57.5% with a mean of 63.12. Third-degree burn, exposed burnt body part, total body surface area burned ≥ 20%, having an amputation and having a co-morbid illness with (P = 0.001) were associated with poor health-related quality of life.Conclusion and Recommendation: This study revealed that more than half of the burn survivors had poor health-related quality of life. There shall be strengthened long-term physical and psychosocial domains (generic) intervention for burn survivors by giving more concern for those with the identified risk factors.Keywords: Amhara, burn injury, Ethiopia, quality of life